eCM 2012
DOI: 10.22203/ecm.v024a06
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on the cell biological characteristics and the stimulation potential of male human tenocyte-like cells

Abstract: The incidence of rotator cuff tears and recurrent defects positively correlate with patient age. However, this observation has never been analysed at the cellular level. The present study aims to better understand this correlation by investigating cellular characteristics of rotator cuff tenocytes of different age groups. Additionally, previous studies reported on stimulating effects of Bone Morphogenetic Protein (BMP)-2 and BMP-7 on tenocytes. Thus, the second aim was to investigate, whether the stimulation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 67 publications
9
88
2
Order By: Relevance
“…It is still unclear whether or not there is a specific factor(s) involved in the biomechanical changes of tendons due to ageing, and this is highly debated in the literature. Some authors found a different collagen type I and type III expression in tendons of young people compared with the elderly [1,4,10,17], whereas other authors found no difference [11]. In the study by Kostrominova and Brooks [12], decreased expression in elastin (ELN) messenger RNA (mRNA) (the main property of ELN is the ability to deform reversibly with little force and without loss of strength) and in proteoglycan 4 (PRG4) (a glycoprotein with lubricating properties) in elderly tendons was also found, and this could be SD standard deviation responsible for the increased tendon stiffness.…”
Section: Discussionmentioning
confidence: 95%
“…It is still unclear whether or not there is a specific factor(s) involved in the biomechanical changes of tendons due to ageing, and this is highly debated in the literature. Some authors found a different collagen type I and type III expression in tendons of young people compared with the elderly [1,4,10,17], whereas other authors found no difference [11]. In the study by Kostrominova and Brooks [12], decreased expression in elastin (ELN) messenger RNA (mRNA) (the main property of ELN is the ability to deform reversibly with little force and without loss of strength) and in proteoglycan 4 (PRG4) (a glycoprotein with lubricating properties) in elderly tendons was also found, and this could be SD standard deviation responsible for the increased tendon stiffness.…”
Section: Discussionmentioning
confidence: 95%
“…Non-traumatic rotator cuff tear is the most common shoulder joint disease and it has age-associated incidence, since it is favored by the co-presence of metabolic diseases such as diabetes, thyroid disorders and hypercholesterolemia [1][2][3][4] . Conservative treatment of tendinopathies has been increasingly supported by scientific evidence over the last twenty years 5 .…”
Section: Introductionmentioning
confidence: 99%
“…During tendinopathy and tendon acute rupture, a higher incidence of tenocyte apoptosis occurrence and decreased collagen synthesis has been reported 8 . The failure of the healing response may occur in genetically-predisposed patients, decreasing the resistance of tendon structures to mechanical load, resulting eventually in tendinopathy, or a tendon tear 4,9,10 . Hyaluronic acid (HA) (or "hyaluronan", or "sodium hyaluronate preparation") is a high molecular weight glycosaminiglycan, consisting on the repetition of a disaccharide unit composed by N-acetyl-glucosamine and a β-glucuronic acid 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this structural arrangement and the tenocyte interrelationships are also affected by age [13], clearly showing a different tendon structure in newborn, young and adult individuals (Fig. 2) [14].…”
Section: Tendons Biochemical Composition and Ultrastructurementioning
confidence: 98%